Re-irradiation of Recurrent Pineal Germ Cell Tumors with Radiosurgery: Report of Two Cases and Review of Literature - Wong, Kenneth (Cureus, 2016)
Primary intracranial germ cell tumors are rare, representing less than 5% of all central nervous system tumors. Overall, the majority of germ cell tumors are germinomas and approximately one-third are non-germinomatous germ cell tumors (NGGCT), which include teratoma, embryonal carcinoma, yolk sac tumor (endodermal sinus tumor), choriocarcinoma, or mixed malignant germ cell tumor. Germ cell tumors may secrete detectable levels of proteins into the blood and/or cerebrospinal fluid, and these proteins can be used for diagnostic purposes or to monitor tumor recurrence. Germinomas have long been known to be highly curable with radiation therapy alone. However, many late effects of whole brain or craniospinal irradiation have been well documented. Strategies have been developed to reduce the dose and volume of radiation therapy, often in combination with chemotherapy. In contrast, patients with NGGCT have a poorer prognosis, with about 60% cured with multimodality chemoradiation. There are no standard approaches for relapsed germ cell tumors. Options may be limited by prior treatment. Radiation therapy has been utilized alone or in combination with chemotherapy or high-dose chemotherapy and transplant. We discuss two cases and review options for frameless radiosurgery or fractionated radiotherapy.